Alternatif Pola Pengasuhan (Pendidikan, Pembinaan dan Pengawasan) Taruna ATKP Makassar dan Implikasinya Bagi Ketahanan Pribadi Taruna - Idyaningsih, Nining (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
Based on the problems raised, the problem of parenting concerns the attention of the researcher and demands a solution related to (a) Not optimal parenting cadets in ATKP? (b) Not optimal facilities at the Makassar ATKP? (c) Not optimal human resources available at ATKP Makassar. The objectives to be achieved in this study are (a) Knowing the pattern of care for Makassar ATKP. (b) Knowing the Human Resources available at ATKP Makassar (c) Knowing the facilities that can be used by cadets in ATKP Makassar (d) Formulate strategies for optimizing parenting patterns and their implications for the personal endurance of cadets. This research is a descriptive qualitative study, the method of collecting data through interviews in the form of question and answer directly to the informants representatives of caregivers as well as cadets and the observations and continued analysis of the data so that the data will be more focused on the problems that have been predetermined. The efforts to optimize parenting patterns are carried out with strategies involving the cadets in all activities that can foster self-confidence and socialize with fellow cadets and the surrounding environment.